A 26 GHz rectenna based on a solar cell antenna for internet of things applications - Baccouch, Chokri; Omar, Saleh; Rhaimi, Belgacem C. (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This paper presents a new rectenna system that combine a patch antenna with a solar cell to capture energy from both radio frequency (RF) signals and sunlight. The patch antenna collects RF signals, while the solar cell converts sunlight into electricity. This integration offers a sustainable energy solution for internet of things (IoT) sensors or drones. The antenna's performance at 26 GHz demonstrates impressive metrics, including a -68 dB S11 reflection, 700 MHz bandwidth, 6.25 dBi gain, 49.8 Ω impedance, and 42.25% RF-DC conversion efficiency. The "solar rectenna" integrates both technologies, driving technological advancement and fostering sustainability in wireless communication.